Modeling Asymmetric Flow in the Thin‐Slab Casting Mold Under Electromagnetic Brake. Issue 12 (30th November 2022) - Vakhrushev, Alexander; Kharicha, Abdellah; Karimi-Sibaki, Ebrahim; Wu, Menghuai; Ludwig, Andreas; Nitzl, Gerald; Tang, Yong; Hackl, Gernot; Watzinger, Josef
Abstract : In article 2200088, Kharicha and co‐workers show that a uniform melt motion is vital for the thin slab casting process featured by the high casting and solidification rates. Here an application of electromagnetic braking to suppress an asymmetric flow is illustrated. The induced electric current lines, generated around the jets, tend to close through the conductive solid, stabilizing the flow pattern and inhibiting the remelting of the shell.